2000
DOI: 10.1063/1.1361939
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of the optical properties of sulfate aerosols

Abstract: Parameterizations of the shortwave optical properties of ammonium sulfate [(NH 4) 2 SO 4 ], ammonium bisulfate (NH 4 HSO 4), and sulfuric acid (H 2 SO 4) are provided as functions of relative humidity for high and low spectral resolution band models. The optical property parameterization is simple in form and in its dependence on relative humidity. The growth of the aerosol particles is based on equilibrium saturation theory, and the optical properties are computed from Mie theory. The optical properties neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Assuming that Kotchenruther et al's results provide a lower bound for the RH growth in CLAMS, we can estimate an upper bound using Li et al's (2001) theoretical RH growth curve parameterizations for pure sulfate aerosols. We base our choice of the degree of acidity of the pure sulfate aerosol on a study by Brook et al (1997), who found that sulfate aerosol acidity increased in maritime locations on the Canadian Atlantic coast compared to the generally neutralized sulfate aerosol encountered further inland.…”
Section: H Sensitivity Of Results To Hygroscopic Growthmentioning
confidence: 98%
See 1 more Smart Citation
“…Assuming that Kotchenruther et al's results provide a lower bound for the RH growth in CLAMS, we can estimate an upper bound using Li et al's (2001) theoretical RH growth curve parameterizations for pure sulfate aerosols. We base our choice of the degree of acidity of the pure sulfate aerosol on a study by Brook et al (1997), who found that sulfate aerosol acidity increased in maritime locations on the Canadian Atlantic coast compared to the generally neutralized sulfate aerosol encountered further inland.…”
Section: H Sensitivity Of Results To Hygroscopic Growthmentioning
confidence: 98%
“…The upper bound to aerosol growth with increasing RH based on Li et al (2001) and Brook et al (1997) was applied to Eqs. (3) and (5), and to our calculations of the apportionment of AOD.…”
Section: H Sensitivity Of Results To Hygroscopic Growthmentioning
confidence: 99%
“…As will be discussed later, values of 0 and various size parameters were virtually identical in the two campaigns, but the aerosol composition differed as discussed by Magi et al (2005), who explain that we can assume the Kotchenruther et al (1999) results provide a lower bound for the RH growth for CLAMS and use the theoretical growth curve parameterizations for pure sulfate aerosols as determined by Li et al (2001) to estimate an upper bound. Since Magi et al (2005) show that aerosol composition during CLAMS was dominated by sulfate, we can determine the degree of acidity of the pure sulfate aerosol based on a study by Brook et al (1997) and air parcel back trajectories during CLAMS.…”
Section: B Optical Parametersmentioning
confidence: 93%
“…The relation of size distributions of dry and wet aerosols was explicitly discussed in Li et al (2001). The relation of size distributions of dry and wet aerosols was explicitly discussed in Li et al (2001).…”
Section: 1029/2018gl081193mentioning
confidence: 99%